Physical processes matters! Recommendations for sampling microplastics in estuarine waters based on hydrodynamics. (June 2023) - Defontaine, Sophie; Jalón-Rojas, Isabel
Abstract: Monitoring the abundance and characteristics of microplastics in estuarine waters is crucial for understanding the fate of microplastics at the land-sea continuum, and for developing policies and legislation to mitigate associated risks. However, if protocols to monitor microplastic pollution in ocean waters or beach sediments are well established, they may not be adequate for estuarine environments, due to the complex 3D hydrodynamics. In this note, we review and discuss sampling methods and strategies in relation to the main environmental forcing, estuarine hydrodynamics, and their spatio-temporal scales of variability. We propose recommendations about when, where and how to sample microplastics to capture the most representative picture of microplastic pollution. This note opens discussions on the urgent need for standardized methods and protocols to routinely monitor microplastics in estuaries which should, at the same time, be easily adaptable to the different systems to ensure consistency and comparability of data across different studies. Graphical abstract: Unlabelled Image Highlights: Strategies and methods for sampling microplastics in estuarine waters are reviewed. The need of considering hydrodynamics when planning in-situ surveys is highlighted. Recommendations on when, where and how sampling are discussed in relation to hydrodynamics.